Penerapan Sistem Manajemen Kesehatan dan Keselamatan Kerja di Rumah Sakit Bersalin Pertiwi Makassar - Nur Asmar Salikunna; Vera Diana Towidjojo (Biocelebes, 2011)
The hospital is a health facility which organizes the activities of health services and can serve place of health education and research.The hospital has special characteristics that can increase the chances of accidents thus requiring theapplication of Health and Safety at Work management system as regulated in Law No. 23 of 1992 on Health,Article 23 stated that Health and Safety at Work efforts be held in all workplaces, especially workplaces that have a health hazard, easily affected by the disease or have employees at least 10 people.This research was this Research used a survey method with a descriptive approach to seeing the implementation Health and Safety at Work Management system at RS.Bersalin Pertiwi Makassar.The results showed that the achievement of Health and Safety at Work Management system in RS.Bersalin Pertiwi Makassar amounted to 57.86% (81 criteria applied).So this hospital into the range of levels of achievement of the application of 0-59%, so the entry in the poor category.